Psychiatric Morbidity of Cannabis Abuse - Sarkar, Jaydip (Medknow Publications, 2003)
The paper evaluates the hypothesis that cannabis abuse is associated with a broad range of psychiatric disorders in India, an area with relatively high prevalence of cannabis use. Retrospective case-note review of all cases with cannabis related diagnosis over a 11 -year period, for subjects presenting to a tertiary psychiatric hospital in southern India was carried out. Information pertaining to sociodemographic, personal, social, substance-use related, psychiatric and treatment histories, was gathered. Standardized diagnoses were made according to Diagnostic Criteria for Research of the World Health Organization, on the basis of information available. Cannabis abuse is associated with widespread psychiatric morbidity that spans the major categories of mental disorders under the ICD-10 system, although proportion of patients with psychotic disorders far outweighed those with non-psychotic disorders. Whilst paranoid psychoses were more prevalent, a significant number of patients with affective psychoses, particularly mania, was also noted. Besides being known as either the causative agent or a potent risk factor in cases of paranoid psychoses, cannabis appears to have similar capabilities with regard to affective psychoses, particularly in cases of mania. It is suggested that cannabis has the potential to act as a "life event stressor" amongst subjects vulnerable to develop affective psychoses and the possible aetiopathogenesis of such a finding is discussed.